LMNB2 is a prognostic biomarker and correlated with immune infiltrates in hepatocellular carcinoma. Issue 12 (19th November 2020) - Kong, Weihao; Wu, Zihao; Yang, Mingwei; Zuo, Xiaomin; Yin, Guanfu; Chen, Wei
Abstract: Background: Previous studies have suggested Lamin B2 (LMNB2) as an oncogene in lung cancer. However, the role of LMNB2 in hepatocellular carcinoma (HCC) remains unclear. Method: The expression of LMNB2 was compared between HCC samples and non‐tumor samples in multiple datasets. In addition, the prognostic value of LMNB2 in HCC was also investigated. Furthermore, the cBioPortal was utilized to analyze the genomic alternation of LMNB2 in HCC. Besides, co‐expression genes and functional enrichment analysis were evaluated using LinkedOmics to determine the function of LMNB2. Finally, the correlation between LMNB2 and immune infiltration was assessed using Tumor Immune Estimation Resource (TIMER). Results: Elevated LMNB2 expression level was identified in HCC patients in multiple datasets. Moreover, increased levels of LMNB2 were associated with poor overall survival (OS) and disease‐free survival (DFS). The functional enrichment analysis revealed that LMNB2 plays an essential role via the cell cycle pathway, spliceosome, hippo‐signaling pathway, and metabolic pathways. Besides, copy number variation (CNV) and methylation were significantly associated with LMNB2 expression. Additionally, increased levels of LMNB2 were significantly associated with B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells. Conclusion: LMNB2 is a potential HCC prognostic and diagnostic biomarker.